2021
DOI: 10.1155/2021/5555634
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ATP6V1A Involved in Alzheimer’s Disease via Synaptic Vesicle Cycle, Phagosome, and Oxidative Phosphorylation

Abstract: Objective. The objective of this study was to investigate the potential molecular mechanisms of ATPase H+ transporting V1 subunit A (ATP6V1A) underlying Alzheimer’s disease (AD). Methods. Microarray expression data of human temporal cortex samples from the GSE118553 dataset were profiled to screen for differentially expressed genes (DEGs) between AD/control and ATP6V1A-low/high groups. Correlations of coexpression modules with AD and ATP6V1A were assessed by weight gene correlation network analysis (WGCNA). DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
4
18
0
Order By: Relevance
“…In the present study, upregulated LTF has also been observed (Figure 2; Table 1), while the mutation of ATP2A2 enzyme in the brain that affects cytosolic Ca 2+ uptake may cause increased dopamine signaling, leading to neurological disorders such as schizophrenia and mood-altering disease [23]. The other observed enzyme ATP6V1H (ATPase H+ transporting V1 subunit H) has been associated with aging and neurodegeneration, which might be responsible for AD pathophysiology [24][25][26][27]. The enzyme modulator, G protein subunit gamma 3 (GNG3), was also found to be deregulated in the disease phenotype (Table 1 [28]).…”
Section: Identification Of Deregulated Genes In Adsupporting
confidence: 64%
“…In the present study, upregulated LTF has also been observed (Figure 2; Table 1), while the mutation of ATP2A2 enzyme in the brain that affects cytosolic Ca 2+ uptake may cause increased dopamine signaling, leading to neurological disorders such as schizophrenia and mood-altering disease [23]. The other observed enzyme ATP6V1H (ATPase H+ transporting V1 subunit H) has been associated with aging and neurodegeneration, which might be responsible for AD pathophysiology [24][25][26][27]. The enzyme modulator, G protein subunit gamma 3 (GNG3), was also found to be deregulated in the disease phenotype (Table 1 [28]).…”
Section: Identification Of Deregulated Genes In Adsupporting
confidence: 64%
“…In addition, ATP6V1C2 also modulates the concentration of neurotransmitters into synaptic vesicles and is crucial in synaptic transmission (Zhao et al, 2018). A very recent study has reported that the pleiotropic roles of low ATP6V1A levels in AD pathogenesis are mediated via the synaptic vesicle cycle, phagosome, and oxidative phosphorylation (Zhou et al, 2021), which is consistent with results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, V-ATPase would influence cellular processes such as endocytosis, vacuole fusion and protein degradation in eukaryotes. As lysosomes are the finaldegradation organelles of Aβ peptide and acidic environment is the determinant of hydrolytic enzyme activation, it is speculated that down-regulation of ATP6V1C2 mRNA levels in AD model cells would lead to increasing of pH value in lysosomes, resulting in inactivation of peptidases and inefficient Aβ clearance (Zhao et al, 2018;Zhou et al, 2021). However, the acidic lysosomal environment recovered after Pls induction by elevated ATP6V1C2 transcript levels in AD_Pls cells (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, the reversible translocation of V0 and V1 subunits are essential in the optimal functioning of the V-ATPases. The ATP6V1-A was found to be downregulated in the conditions of AD that impacted the neurotransmitter release from synaptic vesicles and prevented phosphorylation and phagosome formation thus worsening AD pathologies [ 125 ]. ATP6AP2 is an important accessory protein that promotes neuronal growth in the CNS.…”
Section: Major Participants In Astrocytic Glutamatergic Transmission ...mentioning
confidence: 99%